Tax Amnesty Policy in Maintaining Order in Fulfilling Taxpayers' Tax Obligations - Friska Firdi Handini Putri; Ridhwan Ardra Majid; Sumali Sumali; Suryaningsih Suryaningsih (Jurnal Hukum Prasada, 2025)
The Tax Amnesty policy or tax amnesty that has been regulated in Law No. 11 of 2016 concerning Tax Amnesty in its implementation always reaps pros and cons and this becomes a polemic and the government plays a role or takes part in dealing with these problems. The research method used in this study is using normative legal research with a conceptual approach and a statute approach. The result of this study is that there are pros and cons of the Tax Amnesty policy even though there are 4 (four) principles, namely the principle of legal certainty, the principle of justice (equity), the principle of utility, and the principle of national interest which have become guidelines and are considered to have violated the purpose of the Tax Amnesty policy or tax amnesty and the government's efforts to overcome this are by improving the tax bureaucracy. periodic tax evaluation, and transparency of money allocation or tax budget.